Aggregation-induced emission materials: a platform for diverse energy transformation and applications. Issue 10 (24th February 2023) - Li, Xue; Yang, Hao; Zheng, Ping; Lin, Danmin; Zhang, Zhijun; Kang, Miaomiao; Wang, Dong; Tang, Ben Zhong
Abstract : Motivated by the advantages of AIEgens in diversifying energy species and modulating energy transformation, the application of AIEgens based on the energy conversion of solar, chemical, mechanical, and electrical energies are summarized. Abstract : The sustainable development of the modern economy and society is facing severe challenges, one of which is the irreversible consumption of traditional fossil fuels. Despite diverse new energy sources being exploited, it is still difficult to meet the growing multifarious energy requirements for practical applications. In this context, the exploration of high-performance energy transformation materials that allow diverse energy transformations with high efficiency offers a pertinent solution. Profiting from the facile diversification of energy species and expedient modulation of energy transformation, aggregation-induced emission luminogens (AIEgens), which are a particular category of luminescent materials, are emerging as an ideal platform for diverse energy transformations and applications. In light of the rapid progress of AIEgens in this promising field, this review comprehensively summarizes the major advancements of AIEgens from the perspective of energy transformation. The transformation of four categories of energy, namely, solar, chemical, mechanical, and electrical energies, based on AIEgens is covered in this review, and the following representative applications relying on energy transformation are elaborated in each part. The current challenges and future perspectives in this direction are also emphasized.